Pengaruh komposisi perekat tanin urea formaldehida terhadap keteguhan rekat kayu lapis meranti - Adi Santoso; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Based on previous research tannin formaldehyde resin from Acacia decurens bark can be used for exterior plywood adhesive. To reduce the cost, the effect of urea addition to produce tannin urea formaldeliyde resin has been studied. The other treatment employed is percentage of paraformaldehyde as hardener.The results show that the properties of tannin urea formaldehyde resin conform with Indonesian standard for phenol formaldehyde resin. The effect of weight ratio based on mol ratio on the plywood bonding strenght is significant, while the effect ofpercentage of hardener is not significant. the weight ratio tannin.urea = 1:2 with three percentages of hardener meet German standardfor exterior plywood (type AW-100). The weight ratio tannin urea = 1=2,5 with 2,5% and 5% hardener meet the standard, while the weight ratio tannin:urea = 1:3 do not meet the standard. The plywood bonding strenght tends to decrease if using more urea. Based on economic consideration, it is recommended 10 use weight ratio tannin.urea = 1:2,5 based on mol ratio with percentage of hardener 2,5% of liquid resin.